SANKSI DAN PENGHARGAAN DALAM PENDIDIKAN ISLAM - Ibrahim Bafadhol (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
In human being, they are bad and good character. It is learning tool to increase good character by reward. And learning tool to decrease bad character by punishment. There are many verses of the Holy Quran about reward and punishment as learning tools. There are many examples from prophet history about reward and punishment. Reward and punishment are important priciples in Islamic education.Â Kata kunci: Sanksi, penghargaan, Pendidikan Islam.